2013
DOI: 10.1044/1058-0360(2012/10-0078)
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Bilingualism and Heritage Language Maintenance: Perspectives of Minority-Language Mothers of Children With Autism Spectrum Disorders

Abstract: There is an urgent need for practitioners to be better informed about issues related to intergenerational language practices in minority-language families. Language use between parents and children is a complex matter that is unique to each family. Parents need to be supported to make language use decisions that are self-enhancing and congruent with their families' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
3
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 40 publications
(34 reference statements)
9
174
3
8
Order By: Relevance
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 69%
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 69%
“…Six études ont été menées auprès des populations du Bangladesh, du Pakistan et d'Inde résidant au Royaume-Uni (Bywaters et al, 2003 ;Croot, 2012 ;Croot et al, 2012 ;Heer et al, 2012 ;Kaur-Bola et Randhawa, 2012 ;Kramer-Roy, 2012). Quant à l'Asie orientale (Chine, Corée, Hong Kong), elle est représentée dans trois autres recherches (Sham, 1996 ;Won, Krajicek et Lee, 2004 ;Yu, 2013). Provenant des États-Unis, des travaux ont été réalisés avec des familles du Mexique, de Porto Rico et du Salvador (Steinberg et al, 1997 ;Bailey et al, 1999 ;Alvarado, 2004 ;Balcazar et al, 2012).…”
Section: éTendue Des Recherches Menéesunclassified
“…À ce propos, Pondé et Rousseau (2013) expliquent que la perturbation des habiletés langagières pousserait généralement les parents immigrants à consulter. Par ailleurs, dans certaines cultures asiatiques (Chine, Corée), l'apprentissage de la langue d'origine reste important pour la famille, quels que soient les problèmes de l'enfant (Sham, 1996 ;Yu, 2013). Sur le plan de l'éducation plus générale, Cohen (2013) met l'accent sur les comportements convenables et le respect comme des préceptes fondamentaux au sein des familles latino-américaines, l'emportant sur des objectifs comme l'indépendance.…”
Section: Facteurs Modulant Le Recours Aux Mesures De Soutienunclassified
See 2 more Smart Citations